New-Generation Ferroelectric AlScN Materials - Zhang, Yalong; Zhu, Qiuxiang; Tian, Bobo; Duan, Chungang (Nano-Micro Letters, 2024)
Ferroelectrics have great potential in the field of nonvolatile memory due to programmable polarization states by external electric field in nonvolatile manner. However, complementary metal oxide semiconductor compatibility and uniformity of ferroelectric performance after size scaling have always been two thorny issues hindering practical application of ferroelectric memory devices. The emerging ferroelectricity of wurtzite structure nitride offers opportunities to circumvent the dilemma. This review covers the mechanism of ferroelectricity and domain dynamics in ferroelectric AlScN films. The performance optimization of AlScN films grown by different techniques is summarized and their applications for memories and emerging in-memory computing are illustrated. Finally, the challenges and perspectives regarding the commercial avenue of ferroelectric AlScN are discussed. Highlights: 1 Ferroelectricity and domain dynamics of emerging ferroelectric AlScN films were discussed. 2 The performance optimization of ferroelectric AlScN films grown by different deposition techniques was comprehensively analyzed. 3 The challenges and perspectives regarding the commercial avenue of AlScN-based memories and in-memory computing applications were summarized.